Systematic Literatur Review : Penerapan Konsep Green Campus dalam Meningkatkan Kesadaran Lingkungan di Perguruan Tinggi - Napitupulu, Hendrik; Ammar Ghali; Prilian Catur N; Topan Adi P (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to evaluate the implementation of the Green Campus concept in increasing environmental awareness in higher education institutions through a Literature Review approach. A total of 15 selected scientific articles published between 2019 and 2025 were analyzed based on themes such as the implementation of green campus policies, students’ perceptions and participation, and sustainability indicators such as the UI GreenMetric. The review results indicate that the Green Campus initiative has been implemented in various universities in Indonesia and Malaysia with diverse approaches, covering aspects of infrastructure, waste management, energy efficiency, and environmental education. The findings show that students’ environmental awareness can be significantly improved through education, involvement in green campus programs, and the provision of supporting physical facilities such as green open spaces and environmentally friendly transportation systems. Studies by Ja’afar (2023) and Mohd. Nawi & Choy (2020) emphasize the importance of integrating sustainability culture into student activities and institutional management. However, student involvement remains a challenge in some institutions due to the lack of systematic and sustainable empowerment strategies. This study recommends the need for cross-sector collaboration within the campus environment, as well as strengthening the role of institutions in facilitating active student participation. Furthermore, regular evaluations of sustainability indicators such as the UI GreenMetric can serve as a reference for designing more effective policies. With a holistic approach, the Green Campus not only impacts the quality of the physical campus environment but also enhances the ecological awareness and responsibility of the younger generation. Keywords: Environmental Awareness, Green Campus, Literature Review, Students, Sustainable Campus, UI GreenMetric.